두록의 동결정액의 운동학적 특성과 ESR1 유전자의 SNP(g.35756T>C)와 연관성 분석 - 조은석; 김기현; 우제석; 이미진; 고준호; 김영주; 사수진; Eun-Seok Cho; Ki-Hyun Kim; Jae-Seok Woo; Mi-Jin Lee; Jun-Ho Ko; et al. (Journal of animal reproduction & biotechnology (Online), 2015)
Cryopreservation of boar semen is continually researched in reproductive technologies and genetic resource banking in breed conservation. For evaluating the boar semen quality, sperm motility (MOT) is an important parameter because the movement of spermatozoa indicates active metabolism, membrane integrity and fertilizing capacity. Various researches have been trying to improve the quality of semen Post-thawed in boar. Recently, polymorphism (g. 35756 T>C) of Estrogen Receptor 1 (ESR1) gene reported to be significant association with MOT. This study was conducted to evaluate the ESR1 gene as a positional controlling for motility and kinematic characteristics of post-thawed boar semen. To results, The g.35756 T>C SNP of ESR1 was significantly associated with frozen semen motility and kinematic characteristics. The g.35756 T>C SNP was high significantly associated with MOT, VCL, VSL and VAP (p<0.001). The SNP was also significantly associated with ALH (P<0.05). Therefore, we suggest that the g. 35756 T>C polymorphism in the intron 1 region of the porcine ESR1 gene could potentially be applied in frozen semen programs to improve MOT trait, but only after validation in other populations.